School Factors as Correlates of Students’ Chemistry Achievement in Senior Secondary Schools in North-West Sierra Leone - Saidu Conteh (Scientia Publica Media, 2026)
Even though there is proof that learning in favorable conditions yields positive outcomes, the performance of students in chemistry in North-West Sierra Leone remains on a downward trajectory. This research explored school factors as correlates of students’ chemistry achievement in senior secondary schools in North-West Sierra Leone using an ex-post facto research design. Specifically, the study examined the influence of school location and laboratory adequacy on students’ academic achievement in chemistry. Data from 198 senior secondary school two (SSS II) students from both urban and rural schools were obtained using the Chemistry Achievement Test (CAT) and the School Factors Questionnaire (SFQ), with a reliability coefficient of 0.78 and 0.82, respectively. Independent samples t-test and Pearson correlation were utilized for data analyses using SPSS version 27. It was found that there was a statistically significant difference in chemistry achievement with respect to school location, where urban students outperformed their rural counterparts [t (196) = 6.12, p < .05] with a large effect size (d = 0.91). Additionally, laboratory adequacy and students’ achievements in chemistry showed a positive correlation (r = .46), explaining 21% of the variance in achievement. The findings further suggest that inadequate laboratory facilities and disparities in educational resources between urban and rural schools may contribute significantly to poor chemistry performance among students. This research paper concludes that school locations and adequate laboratories are some of the key determinants of students’ academic achievement in chemistry. It should therefore be a priority for policymakers to ensure that there is equal resource allocation in urban and rural schools, including laboratory facilities, to strengthen chemistry education and improve students’ academic outcomes in North-West Sierra Leone.